The Context of Distraction: Moderating Effects of Academic Discipline and Socioeconomic Status on Cell Phone Multitasking and GPA among Indian Undergraduates - Joshi, Suresh C. (Journal of Psychological Perspective, 2025)
This study investigated how cell phone multitasking (CPM) influences academic performance, measured by Grade Point Average (GPA), among Indian undergraduate students. A total of 476 students from a large private university in Northern India completed a structured survey assessing CPM frequency, socioeconomic status (SES), academic discipline, and institutional phone-use policies. Hierarchical regression analysis was conducted to examine the predictive relationship between CPM and GPA and to test the moderating effects of SES and academic discipline. Results indicated a significant negative association between CPM and GPA (ρ = –0.15, p 0.001), with students who multitasked more frequently exhibiting lower academic performance. In the final regression model, CPM emerged as a statistically significant but modest predictor of GPA (β = –0.06, p 0.05), explaining a small proportion of variance in academic outcomes (ΔR² = 0.035, total R² = 0.130). The effect size was small but significant (ηp² = 0.016, 95% CI [0.000002, 0.0106]). The negative association was stronger among STEM students (ρ = –0.20, p 0.001) and those from lower SES backgrounds (ρ = –0.25, p 0.001), suggesting that both cognitive load and socioeconomic constraints exacerbate the academic costs of multitasking. Furthermore, stricter institutional phone policies mitigated CPM’s adverse impact on GPA. These findings demonstrate that frequent multitasking with mobile phones hinders academic achievement, particularly among students facing higher cognitive demands or limited resources. The study underscores the importance of structured phone-use policies, targeted digital literacy programs, and equitable academic support to help students regulate digital distractions and enhance learning outcomes in higher education contexts.